Abordagem multidisciplinar no diagnóstico e no tratamento de lesões intraósseas próximas ao ápice dentário: etapas do exame clínico e parâmetros diferenciais entre as lesões - Omena, Tatiane Azeredo (2016)
There are many difficulties encountered by dentists when it comes to the diagnosis of Intraosseous Lesions Located Near the Root Apex (ILLNRA). These lesions have biological, clinical, radiographic and / or tomographic similarities. The ILLNRA are common in dental routine. They are composed by reactive periapical lesions, cystic lesions or non-odontogenic intraosseous lesions. A professional who is not able distinguish these lesions, can make mistakes in the final diagnosis and establish contraindicated therapies. The standardization of diagnostic and treatment management, behavior a protocol can decrease the chance of error, always considering the clinical, radiographic and histological individuality. This study aimed to describe a protocol containing several multidisciplinary approaches to an allowing the diagnosis and appropriate treatment of ILLNRA. The study also aimed to describe the demographic characteristics of the ILLNRAs population as well as the clinical and aspects of these lesions. This protocol consisted of five steps for the management of 19 patients with ILLNRA. Clinical, imaging and auxiliary approaches used in this study permitted to conclude the diagnosis and treatment of all lesions. The results showed that the population with the ILLNRA consisted mostly of adults, whites and females. Clinically and radiographically these lesions were mostly symptomatic, with swelling, pain on percussion, unilocular, radiolucent and well-defined limits. Treatment of these lesions consisted of surgery and endodontics. Radicular cyst was the ILLNA most commonly observed. The application of this protocol allowed the final diagnostic and the use of non invasive techniques for the treatment of ILLNRA.